Canadian Stroke Best Practice Recommendations for Acute Stroke Management: Prehospital, Emergency Department, and Acute Inpatient Stroke Care, 6th Edition, Update 2018. Issue 9 (December 2018) - Boulanger, JM; Lindsay, MP; Gubitz, G; Smith, EE; Stotts, G; Foley, N; Bhogal, S; Boyle, K; Braun, L; Goddard, T; Heran, MKS; Kanya-Forster, N; et al.
The 2018 update of the Canadian Stroke Best Practice Recommendations for Acute Stroke Management, 6th edition, is a comprehensive summary of current evidence-based recommendations, appropriate for use by healthcare providers and system planners caring for persons with very recent symptoms of acute stroke or transient ischemic attack. The recommendations are intended for use by a interdisciplinary team of clinicians across a wide range of settings and highlight key elements involved in prehospital and Emergency Department care, acute treatments for ischemic stroke, and acute inpatient care. The most notable changes included in this 6th edition are the renaming of the module and its integration of the formerly separate modules on prehospital and emergency care and acute inpatient stroke care. The new module, Acute Stroke Management: Prehospital, Emergency Department, and Acute Inpatient Stroke Care is now a single, comprehensive module addressing the most important aspects of acute stroke care delivery. Other notable changes include the removal of two sections related to the emergency management of intracerebral hemorrhage and subarachnoid hemorrhage. These topics are covered in a new, dedicated module, to be released later this year. The most significant recommendation updates are for neuroimaging; the extension of the time window for endovascular thrombectomy treatment out to 24 h; considerations for treating a highly selected group of people with stroke of unknown time of onset; and recommendations for dual antiplatelet therapy for a limited duration after acute minor ischemic stroke and transient ischemic attack. This module also emphasizes the need for increased public and healthcare provider's recognition of the signs of stroke and immediate actions to take; the important expanding role of paramedics and all emergency medical services personnel; arriving at a stroke-enabled Emergency Department without delay; and launching local healthcare institution code stroke protocols. Revisions have also been made to the recommendations for the triage and assessment of risk of recurrent stroke after transient ischemic attack/minor stroke and suggested urgency levels for investigations and initiation of management strategies. The goal of this updated guideline is to optimize stroke care across Canada, by reducing practice variations and reducing the gap between current knowledge and clinical practice.